2004
DOI: 10.1074/jbc.m311463200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination-mediated Regulation of Biosynthesis of the Adhesion Receptor SHPS-1 in Response to Endoplasmic Reticulum Stress

Abstract: Misfolding of proteins during endoplasmic reticulum (ER) stress results in the formation of cytotoxic aggregates. The ER-associated degradation pathway counteracts such aggregation through the elimination of misfolded proteins by the ubiquitin-proteasome system. We now show that SHP substrate-1 (SHPS-1), a transmembrane glycoprotein that regulates cytoskeletal reorganization and cell-cell communication, is a physiological substrate for the Skp1-Cullin1-NFB42-Rbx1 (SCF NFB42 ) E3 ubiquitin ligase, a proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Although results by others have supported the formation of full SCF complexes when Fbx2 is coexpressed with other subunits of SCF complexes in transfected cells (Yoshida et al, 2002;Murai-Takebe et al, 2004), we consistently failed to observe coprecipitation of Cullin1 and Rbx1 with endogenous Fbx2 in cochlear and brain extracts (Fig. 6a,b).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Although results by others have supported the formation of full SCF complexes when Fbx2 is coexpressed with other subunits of SCF complexes in transfected cells (Yoshida et al, 2002;Murai-Takebe et al, 2004), we consistently failed to observe coprecipitation of Cullin1 and Rbx1 with endogenous Fbx2 in cochlear and brain extracts (Fig. 6a,b).…”
Section: Resultsmentioning
confidence: 78%
“…Levels of Cullin7 (another cullin expressed in the cochlea) are unchanged in KO mice. al., 2002;Murai-Takebe et al, 2004;Hagihara et al, 2005;Kato et al, 2005;Nelson et al, 2006). We propose that the loss of hearing observed in Fbxo2 Ϫ/Ϫ mice is caused by a failure of glycoprotein quality control in the organ of Corti.…”
Section: Discussionmentioning
confidence: 99%
“…As changes related to the pulmonary remodeling following exposure to PQ, the up-regulation of the expression of cofilin, which is involved in the depolymerization and cleavage of actin filaments, the LIM motif-containing protein kinase 1, which negatively regulates the activity of cofilin (Hotulainen et al, 2005;Prochniewicz et al, 2005;Willis et al, 2005), SHPS-1, which regulates the integrin-mediated reorganization of the cytoskeleton (Inagaki et al, 2000;Maile et al, 2003;Murai-Takebe et al, 2004) and sodium channel beta 2, which is involved in cell adhesion and migration (Kim et al, 2005) were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this ubiquitin ligase degrades the adhesion receptor SHPS-1, which may be involved in tumor metastasis in melanomas and other cancers. [56][57][58] Finally, we show here that FBG1 interacts with APC2 and Cul7, both of which play important roles in lower levels. Second, in contrast to other FBG family members, FBG1 is not expressed during embryonic development and its expression increases in the brain during the first ten months of life.…”
Section: Scf Ubiquitin Ligase Complex (Pdb Code 1ldk) Is Shown For Rementioning
confidence: 99%